Comparison of Food Attractants for Monitoring Fruit Fly (Diptera: Tephritidae) in Citrus Orchards in Brazil - Alves Rodrigues, Marjorie Delgado; Raga, Adalton; Maldonado Junior, Walter [UNESP]; Barbosa, Jose Carlos [UNESP]; SabaterMunoz, B.; Moreno, P.; Pena, L.; Navarro, L. (Int Soc Horticultural Science, 2015)
Anastrepha fraterculus (Wiedemann) and Ceratitis capitata (Wiedemann) are the most important fruit fly species in Brazil. Both species causes significant losses in citrus production in the State of Sao Paulo. The aim of this study was to compare the efficacy of different food bait attractants for monitoring fruit flies in Integrated Pest Management (IPM) programs. The experiment was conducted under block randomized design with seven attractants (BioAnastrepha, IscaMosca, Samarita, Torula (R), Milhocina (R) plus borax, sugar cane molasses and grape juice). The experiments were performed in two seasons, from March until April (season 1) and from November until December 2008 (season 2), in two orange orchards (organic and conventional systems) located in Mogi-Guacu, SP. The number of flies captured by each attractant was evaluated weekly during seven weeks. In total 4,327 adults of Tephritidae were captured: 3,073 specimens of A. fraterculus and 1,258 specimens of C. capitata. Milhocina (R) plus borax and Torula (R) during season 1, and Torula (R) during season 2 were more effective to capture fruit flies. In organic orchard, Torula (R) and BioAnastrepha captured significantly more tephritids during season 2. In general, Torula (R) attracted more females than males.
Keywords: Ceratitis capitata; Anastrepha fraterculus; monitoring; McPhail trap